2021
DOI: 10.3390/cancers13112536
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Fascin-1 in the Pathogenesis, Diagnosis, and Treatment of the Gastrointestinal Cancers

Abstract: Gastrointestinal (GI) cancers, including esophageal, gastric, colorectal, liver, and pancreatic cancers, remain as one of the leading causes of death worldwide, with a large proportion accounting for fatalities related to metastatic disease. Invasion of primary cancer occurs by the actin cytoskeleton remodeling, including the formation of the filopodia, stereocilia, and other finger-like membrane protrusions. The crucial step of actin remodeling in the malignant cells is mediated by the fascin protein family, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 126 publications
(315 reference statements)
0
21
0
Order By: Relevance
“…Even though fascin1 has been identified as a driver and prognostic marker of metastatic CRCs a systematic characterization of fascin1 function in the etiology of CRCs is lacking. (Ristic et al, 2021) Fascin1 expression is very significantly upregulated in SSLs and fascin1 has been identified as a potential biomarker of SSLs. (Ashktorab et al, 2019;Kanth et al, 2019;Kanth et al, 2016) Herr et al, 2015) Here we show that in BRAF V600E CRC cells, AJ and TJ remodeling is phenocopied by fascin1 upregulation and we identify fascin1 as a major driver of this BRAF V600E -mutant CRC phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though fascin1 has been identified as a driver and prognostic marker of metastatic CRCs a systematic characterization of fascin1 function in the etiology of CRCs is lacking. (Ristic et al, 2021) Fascin1 expression is very significantly upregulated in SSLs and fascin1 has been identified as a potential biomarker of SSLs. (Ashktorab et al, 2019;Kanth et al, 2019;Kanth et al, 2016) Herr et al, 2015) Here we show that in BRAF V600E CRC cells, AJ and TJ remodeling is phenocopied by fascin1 upregulation and we identify fascin1 as a major driver of this BRAF V600E -mutant CRC phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…(Li et al, 2014) In multivariate analysis, fascin1 has been identified as an independent factor for CRCs, and fascin1 positive CRCs exhibit a greater ability to invade lymph nodes and develop extra-nodal tumor extensions, and have a higher likelihood of recurrence with a lower rate of disease-free and overall survival. (Hashimoto et al, 2006;Ristic et al, 2021;Tampakis et al, 2021) It is generally assumed that fascin1 drives tumor cell migration and invasion by assembling filopodia and invadopodia. However, there is emerging evidence that fascin1 also has cell migration-independent functions linked to tumor cell proliferation, oncogenesis, metastatic colonization, anoikis resistance, chemoresistance, and cancer stemness although the molecular mechanism underlying these non-canonical functions of fascin1 remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Formation of filopodia [ 70 , 71 ] downstream of activation of TWIST1 and SNAIL1 [ 72 ] and the expression of formins [ 73 , 74 ] regulate the migration of cancer cells undergoing EMT. Additionally, the upregulation of formins contributes to metastasis formation [ 75 ], and high levels of fascin correlate with poor prognosis in a number of cancers including breast, lung, gastrointestinal and oral squamous cell carcinoma [ 64 , 76 , 77 ], suggesting that their role in EMT contributes to cell invasion and the formation of secondary tumour foci. Increased expression of fascin is also associated with the development of EMT-mediated drug resistance in hepatocellular carcinoma [ 78 ].…”
Section: Invasive Adhesions Formed By Cells Undergoing Emt In Solid T...mentioning
confidence: 99%